Modern cowpea farming: proven techniques for higher profits - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Learn how to increase your cowpea yields, improve grain quality, and boost farm profitability through research-backed practices developed specifically for African farming conditions. Perfect for smallholder farmers looking to maximize their cowpea harvest and income.